Polarimetric radar observations and interpretation of co-cross-polar correlation coefficients - Brandes, Edward A., author; Vivekanandan, J., author; Bringi, V. N., author; Hubbert, John C., author; Zrnić, Dusan S., author; Ryzhkov, Alexander V., author; American Meteorological Society, publisher (Colorado State University. Libraries, 2002)
Preliminary analysis of all components of the polarimetric radar covariance matrix for precipitation measured with the NCAR S-band dual-polarization Doppler radar (S-Pol) and the Colorado State University-University of Chicago-Illinois State Water Survey (CSU-CHILL) radars is presented. Radar reflectivity at horizontal polarization Zh, differential reflectivity ZDR, linear depolarization ratio LDR, specific differential phase KDP, crosscorrelation coefficient | ρhv | , and two co-cross-polar correlation coefficients, ρxh and ρxv, have been measured and examined for two rain events: the 14 August 1998 case in Florida and the 8 August 1998 case in Colorado. Examination of the coefficients ρxh and ρxv is the major focus of the study. It is shown that hydrometeors with different types of orientation can be better delineated if the coefficients ρxv and ρxv are used. Rough estimates of the raindrop mean canting angles and the rms width of the canting angle distribution are obtained from the co-cross-polar correlation coefficients in combination with other polarimetric variables. Analysis of the two cases indicates that the raindrop net canting angles averaged over the propagation paths near the ground in typical convective cells do not exceed 2.5°. Nonetheless, the mean canting angles in individual radar resolution volumes in rain can be noticeably higher. Although the net canting angle for individual convective cells can deviate by a few degrees from zero, the average over a long propagation path along several cells is close to zero, likely because canting angles in different cells vary in sign. The rms width of the canting angle distribution in rain is estimated to vary mainly between 5° and 15° with the median value slightly below 10°.